Pengujian Arus pada Simulator Sistem Kelistrikan Air Conditioner (AC) - Hamid Nasrullah; Slamet Ridho Illahi (AEEJ : Journal of Automotive Engineering and Vocational Education, 2020)
Air Conditioner is part in a car to achieve safety and security in driving. The purpose of this study was to determine the current of the air conditioner electrical system, identify the electrical circuit and analyze the electrical circuit of the air conditioner system. This research used experimental method. The air conditioner system simulator show current and voltage generated at blower speed 1: current 15.1 A, produces a temperature of 26 ℃, blower speed 2: current 15.2 A, produces a temperature of 25 ℃, blower speed 3: current 15.5 A, yields a temperature of 24 ℃. Whereas in the car the current and voltage generated by blower speed 1: current 17.4 A, produces a temperature of 21 ℃, blower speed 2: current 17.7 A, produces a temperature of 20 ℃, blower speed 3: current 17.9 A, produces a temperature of 19 ℃. So, the higher the current has an effect on the resulting performance of the air conditioner system. And the lower the current generated, the blower, magnetic clutch and extra fan performance is not optimal when the AC system is running. Sistem Air Conditioner merupakan bagian dari mobil untuk mencapai keyamanan dan keamanan dalam berkendara. Tujuan dari penelitian ini adalah untuk mengetahui arus sistem kelistrikan air conditioner, mengidentifikasi rangkaian kelistrikan dan menganalisis rangkaian kelistrikan sistem air conditioner. Metode penelitian yang digunakan dalam penelitian ini adalah metode eksperimental. Hasil pengujian arus dan tegangan yang dihasilkan pada simulator blower speed 1: arus 15,1 A, menghasilkan suhu 26℃, blower speed 2: arus 15,2 A, menghasilkan suhu 25℃, blower speed 3: arus 15,5 A, menghasilkan suhu 24℃. Sedangan pada mobil arus dan tegangan yang dihasilkan blower speed 1: arus 17,4 A, menghasilkan suhu 21℃, blower speed 2: arus 17,7 A, menghasilkan suhu 20℃, blower speed 3: arus 17,9 A, menghasilkan suhu 19℃. Jadi, semakin tinggi arus berpengaruh pada kinerja yang dihasilkan sistem air conditioner. Dan semakin rendah arus yang dihasilkan membuat kinerja blower, magnetic clutch dan extra fan menjadi tidak maksimal pada saat sistem AC bekerja.